Digit ratio (2D:4D) is associated with gastric cancer - Nicolás Hopp, Renato [UNESP]; de Souza Lima, Nathália Caroline; Filho, José Laurentino; Filho, Marcondes Sena; Lima, Carmen Silvia Passos; Jorge, Jacks (Elsevier, 2013)
Background: Sex steroid exposure during early human development may influence disease susceptibility. Digit ratio (2D:4D) is a putative marker for prenatal hormone exposure and sensitivity, as well as the action of genes closely related to carcinogenesis. Digit ratio could act as a possible marker for cancer predisposition. Aims: The aim of this study is to investigate the possible correlations between right hand, left hand and right minus left (R. - L) 2D:4D and gastric cancer (GCA) in men and women and assess the correlations with tumor staging and histological diagnosis. Methods: Digital images of the right and left hand palms of patients diagnosed with GCA (n = 57, 42 males, 15 females) and age and sex-matched controls (n = 59, 41 males, 18 females) were obtained. Means for 2D:4D were compared. Data were analyzed by repeated-measures one-way ANOVA and Student's t-test for finger measurements and group comparisons and Pearson's and Spearman's tests for correlations with tumor staging (α = 0.05). Results: GCA group presented significantly higher left 2D:4D, but significantly lower R. - L in comparison to healthy controls, particularly so for males. Digit ratio did not correlate to clinical staging or TNM staging. However, low R. - L was significantly related to adenocarcinomas. Conclusions: Early developmental conditions, including prenatal testosterone seem to play a role on the malignant transformation of gastric lesions. The 2D:4D pattern found for gastric cancer parallels that earlier described for breast cancer. The findings suggest that 2D:4D could add to the list of etiological factors and be a putative marker for the screening of patients' susceptibility to develop gastric cancer. © 2012 Elsevier Ltd.
Keywords: 2D:4D; Digit ratio; Gastric cancer; estrogen; testosterone; adult; aged; analysis of variance; cancer staging; cancer susceptibility; controlled study; disease association; female; gender; hand palm; histology; human; major clinical study; male; malignant transformation; measurement repeatability; retrospective study; stomach adenocarcinoma; stomach cancer; stomach lesion; Student t test; tumor volume